Potential application of a bioemulsifier-producing actinobacterium for treatment of vinasse - Colin, Veronica Leticia (2015)
Vinasse is a complex effluent created during production of ethyl alcohol, which can present serious pollution hazard in areas where it is discharged. A variety of technologies, many based upon recovery of the effluent via microbial pathways, are continually being evaluated in order to mitigate the pollution potential of vinasse. The present work reports on initial advances related to the effectiveness of the actinobacterium Streptomyces sp. MC1 for vinasse treatment. Alternative use of raw vinasse as a substrate for producing metabolites of biotechnological interest such as bioemulsifiers, was also evaluated. The strain was able to grow at very high vinasse concentrations (until 50% v/v) and remove over 50% of the biodegradable organic matter in a time period as short as 4 d. Potentially toxic metals such as Mn, Fe, Zn, As, and Pb were also effectively removed during bacterial growth. Decrease in the pollution potential of treated vinasse compared to raw effluent, was reflected in a significant increase in the vigour index of Lactuca sativa (letucce) used as bioremediation indicator. Finally, significant bioemulsifier productionwas detected when this strain was incubated in a vinasse-based culture medium. These results represent the first advances on the recovery and re-valuation of an actual effluent, by using an actinobacterium from our collection of cultures.